URGENSI SEMIOTIKA DALAM MEMAHAMI BAHASA AGAMA - Muzakki, Akhmad (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2008)
In semiotics, language is a sign having two components such as ‘significant’ and ‘signifie’ in which the relation of both is arbitrary. For philosophers interested in language, ‘signifie’ is not meaningless as language is metaphor. Meaning will always change. Meaning is also metaphorical and also depends on the difference of the readers’ background. This concept also works for religious texts that do not use the the last ‘signifie’ because omitting the meaning of the text will stop the development of Islam for man’s goodness. In fact, Islam is a religion that as always relevant with the time.